PENGEMBANGAN DESA WISATA MELALUI PEMBEKALAN BAHASA INGGRIS DASAR BERBASIS PENGENALAN LINGKUNGUN BAGI MASYARAKAT DI DESA WISATA TIGA RIHIT KAMPUNG WARNA WARNI KABUPATEN SIMALUNGUN - Booni Tauhid (Akademi Pariwisata Darma Agung, 2023)
This research will identify and analyze basic English language training programs based on environmental awareness. It will also assess the program's effect on the growth of the tourism village and the involvement of the local community. The data collection methodology used in this qualitative research approach includes observation, interviews, and documentation. understand local culture and environment. The involvement of local communities in the creation of tourist villages has a positive impact on this program, which also creates new economic prospects through tourism. However, program implementation has been hampered by a number of problems, including substandard teaching quality, inadequate infrastructure and facilities, and a lack of marketing and promotion. As a result, efforts should be made to improve education standards, provide infrastructure and facilities, expand marketing and promotion, and provide local communities with the tools they need to protect the environment and local culture. In conclusion, a very significant program for the growth of the tourism village is a basic English language training program based on environmental awareness for the community in the Tourism Village of Kampung Warna Warni Tigarihit, Simalungun Regency. With the efforts made, this program is believed to have a positive impact on the growth of tourist villages in order to improve the welfare of the local community and maintain environmental and cultural sustainability